Desain dan Produktivitas Crushing Plant dalam Upaya Memenuhi Target Produksi Batubara Sebesar 500 Ton/Jam di PT. Dizamatra Powerindo Lahat Provinsi Sumatera - Haryanto, Agus; Hendro Purnomo; Erry Sumarjono (ReTII, 2023)
PT. Dizamatra Powerindo is a company engaged in coal mining with an open pit mining system. This company has 3 (three) ROMs that are actively operating in coal crushing and will build new ROMs (ROM 4) with a capacity of 500 tons / hour. So that a design is needed by taking into account the provisions that become the crusher plant design standard in order to achieve a production plan of 500 tons / hour. The results of this research are based on the design made, the crushing plant design with a production target of 500 tons / hour, can be made with a design that uses 1 belt feeder, 3 belt conveyors, 1 vibrating screen and 1 double roll crusher. The productivity of the crashing plant plan is, BF01 productivity 502,608 Tons/Hour, CP01 productivity, 510,812 Tons/hour, RC productivity 610,412 Tons/Hour, CP02 productivity 518,853 Tons/Hour, and CP03 productivity 525,407 Tons/Hour. With these productivity results, theoretically it can be concluded that the production target of 500 tons / hour can be met.